Ill. bij "Almelosche stoomververij : beveelt zich aan voor het doodverven en zwartmaken van sociaaldemocraten..." - Hahn, Albert,
Ill. bij "Almelosche stoomververij : beveelt zich aan voor het doodverven en zwartmaken van sociaaldemocraten...".